Risk factors for preterm birth and its effect on neonatal mortality in India: evidence from the National Health Family Survey-5 - Priyanka Dixit; Mrigesh Bhatia; Charusheela Bhatia; Laxmi Kant Dwivedi; Saurabh Singh (Discover Public Health)
Abstract Objectives Worldwide, preterm birth is a major contributor to under-five mortality and neonatal mortality. This study aimed to determine the patterns, and sub-national variations of preterm birth in India and identify factors associated with it. Additionally, the association of preterm birth with neonatal mortality was also explored. Methods This study used data from the fifth round of the National Family Health Survey (NFHS-5) conducted during 2019–21. Bivariate analysis and complementary log-log discrete time hazard model were used to achieve the study objectives. Results The prevalence of preterm births in India has dramatically increased over the years, with huge variations among the states. Younger and older maternal age (< 19 years and > 35years), poor economic status, birth intervals < 24 months, delivery by Caesarean section, inadequate antenatal care, residence in the central and northern regions of the country were associated with a higher likelihood of experiencing preterm births. Preterm births were associated with a notably high risk of neonatal mortality when compared to full-term births after adjusting effect of other socioeconomic and program-related factors. The risk of neonatal deaths was 20% higher among male child than females (OR = 1.20, 1.08–1.33), shorter mother height, mothers who smokes (OR = 1.27, 1.04–1.56) and births delivered through C section (OR = 1.31, 1.15–1.50). Conclusions Preterm birth is a matter of major concern to policy makers as it contributes significantly to neonatal mortality. India urgently needs to accelerate investment in, and scale up primary interventions that prevent preterm births for achieving target 3.2 of the Sustainable Development Goals (SDGs) 2030.